Rumble meets Lucas Lizard - Law, Felicia; Pak, Yoon Mi (Minneapolis, Minn. : Picture Window Books, 2005)
Rumble's Cave Hotel is open but there are no guests, so Rumble allows a designer to give the place a makeover, all the while worrying that he will not like the results.
Keywords: Interior decoration -- Fiction; Hotels, motels, etc. -- Fiction; Lizards -- Fiction; Dragons -- Fiction; Spiders -- Fiction